Peripheral Neuroblastic Tumours - Akbar, Jasila; Saldanha, Prema (International Journal of Innovative Research in Medical Science, 2019)
Background: Peripheral neuroblastic tumours arise from the neural crest cells in the sympathetic nervous tissue. These are rare, but are the most common among the extracranial solid tumours occurring in children. Method: This was a retrospective study conducted on 15 cases of peripheral neuroblastic tumours. The demographic details were recorded and the slides were analysed for the microscopic features and classified according to International Neuroblastoma Pathology Classification (INPC). Results: Out of the 15 peripheral neuroblastic tumour cases, 8 were males and 7 females. Seven cases came under age group <1.5years, 5 were between 1.5 years to 5 years and 5 cases were over 5 years of age. Seven tumours were from the retroperitoneal region, 4 cases were from the adrenal gland, 2 from intracranium and one case each was from the neck and the mediastinal regions. There were 8 Neuroblastoma cases, 2 cases of Ganglioneuroblastoma and 5 cases of Ganglioneuroma. It was found that 8 tumours were in the favourable histology group and 7 tumours in the unfavourable histology group. Conclusion: Peripheral neuroblastic tumours are rare. It is important to classify them accurately according to the various categories which help to determine the prognosis.